Exploring the relationship between body mass index and physical fitness: Implications from a comprehensive study in a secondary school setting - Aliriad, Hilmy; Adi S; Fahrudi, Ahmad; Apriyanto, Rohmad; Da'i, Mohamad (Edu Sportivo: Indonesian Journal of Physical Education, 2023)
Assessing the physical fitness and body mass index (BMI) of students is crucial for understanding their overall health and well-being. This study aims to investigate the relationship between students' nutritional status, as measured by BMI, and their level of physical fitness. Physical and anthropometric tests were conducted to collect data on height, weight, and relevant physical indicators, which were used to calculate BMI. The data were analysed using percentage analysis to determine the frequency and percentage of students in different BMI categories and levels of physical fitness. However, it is important to note that this study had limitations, including a sample restricted to students from a single school, which might limit generalizability to the larger student population. Additionally, the study focused solely on the relationship between nutritional status (assessed through BMI) and physical fitness without considering other potential factors that might influence students' fitness levels. Future research should aim to expand the sample size to include a more diverse student population and investigate additional factors that might impact students' physical fitness levels. This study's findings contributed to the existing literature by providing valuable insights into the interplay between students' nutritional status, BMI, and their level of physical fitness.